The Relationship between Disaster Experience and the Preparedness of High School Students in the Merapi Disaster-Prone Area - Sari, Ulia; Widiyatmoko, Wahyu (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This research aims to analyze the relationship between disaster experience on preparedness in the disaster-prone area of Merapi. Methodology: The research technique applied in this research is quantitative research using a correlational design. The population used in this research was all 225 grade 11 students at SMA Negeri 1 Dukun. Sampling was done using the saturated sampling technique. The data collection technique used in this research used a questionnaire. Results: The research results show that 1) The level of disaster experience at SMA Negeri 1 Dukun is in the high category with a percentage of 79% of 225 students and an average disaster experience score of 60. 2). The level of preparedness at SMA Negeri 1 Dukun is in the ready category with a percentage of 38% of 225 students with an average disaster preparedness score of 71.0. 3) The correlation test results obtained a correlation value of 0.320, which is included in the weak Pearson correlation level. Applications/Originality/Value: This research can explain that there is a relationship between disaster experience and students' preparedness in facing the Merapi Volcano eruption disaster at SMA Negeri 1 Dukun.